Perspective Insights to Bio-Nanomaterials for the Treatment of Neurological Disorders - Khan, Johra; Rudrapal, Mithun; Bhat, Eijaz Ahmed; Ali, Ahmad; Alaidarous, Mohammad; Alshehri, Bader; Banwas, Saeed; Ismail, Randa; Egbuna, Chukwuebuka (Frontiers in Bioengineering and Biotechnology, 2021)
Nanomaterials and nanotechnology have grown in popularity in recent years, resulting in major advances in biomedical science and clinical practice. The use of a variety of functionalized nanomaterials at the molecular and cellular levels has resulted in a number of promising advancements in regenerative medicine fields such as tissue engineering, drug and gene delivery. Hydrogels in addition to Self-assembling peptides and Nano carriers have undeniably been recognized as a possible candidate for neuro-regenerative strategies in the treatment of neurological conditions such as Alzheimer's disease, psychosis, spinal cord injury, dementia, and a variety of others. The research of biomaterials for therapeutic purposes is emerging as an area of neurosciences as a consequence of these factors. As such, this chapter discusses the significance of possible biomaterials and advances in treatment of neurological disorders associated with them.